Comparison of perfusion models for quantitative T1 weighted DCE-MRI of rectal cancer - Uhrig, Tanja; Neumann, Wiebke; Janssen, Sonja; Attenberger, Ulrike; Schönberg, Stefan; Schad, Lothar R.; Zöllner, Frank G. (Scientific reports, 2017)
In this work, the two compartment exchange model and two compartment uptake model were applied to obtain quantitative perfusion parameters in rectum carcinoma and the results were compared to those obtained by the deconvolution algorithm. Eighteen patients with newly diagnosed rectal carcinoma underwent 3 T MRI of the pelvis including a T1 weighted dynamic contrastenhanced (DCE) protocol before treatment. Mean values for Plasma Flow (PF), Plasma Volume (PV) and Mean Transit Time (MTT) were obtained for all three approaches and visualized in parameter cards. For the two compartment models, Akaike Information Criterion (AIC) and $${{\boldsymbol{χ }}}^{{\bf{2}}}$$χ2 were calculated. Perfusion parameters determined with the compartment models show results in accordance with previous studies focusing on rectal cancer DCE-CT (PF2CX = 68 ± 44 ml/100 ml/min, PF2CU = 55 ± 36 ml/100 ml/min) with similar fit quality (AIC:169 ± 81/179 ± 77, $${{\boldsymbol{χ }}}^{{\bf{2}}}$$χ2:10 ± 12/9 ± 10). Values for PF are overestimated whereas PV and MTT are underestimated compared to results of the deconvolution algorithm. Significant differences were found among all models for perfusion parameters as well as between the AIC and $${{\boldsymbol{χ }}}^{{\bf{2}}}$$χ2 values. Quantitative perfusion parameters are dependent on the chosen tracer kinetic model. According to the obtained parameters, all approaches seem capable of providing quantitative perfusion values in DCE-MRI of rectal cancer.